Ability of fitness testing to predict injury risk during initial tactical training: a systematic review and meta-analysis. Issue 1 (1st August 2019) - Tomes, Colin D; Sawyer, Sally; Orr, Robin; Schram, Ben
Abstract : Objective: Tactical personnel (Military, Law Enforcement, Emergency Responders) require physical fitness levels sufficient for training and occupational duty. Physical conditioning aimed at increasing fitness levels during training presents an injury risk, but unfit trainees may struggle to meet occupational performance standards, further increasing injury risk to themselvesor others. Therefore, the aim of this review was to determine if fitness, asquantified by tactical fitness tests, effectively predicts injury risk during training. Methods: Literature databases were search and relevant articles extracted. 27 Publications were included for qualitative review and seven studies reporting a timed run were included in meta-analysis. Results: The combined risk ratio was 2.34 (95% CI 2.02 to2.70). Muscular endurance tests were less conclusive in their predictive abilities. Functional strength or power tests were effective predictors, but few studies reported on strength or power, indicating a need for further study inthis area. Conclusions: The meta-analysis results are supported by the occupational relevance of run tests; tactical trainees are required to perform frequent bouts of distance weight bearing activity. However, given the diverse physical requirements of tactical personnel, measures of strength and power should alsobe evaluated, especially given their effectiveness in the studies that included these measures.